Institutions, trade and economic growth - ABDUL-WAHAB, Junior (KDI School, 2018)
Institutional quality and trade have been found to influence economic performance in several empirical studies investigating the separate effect of trade and institutions on growth. Recent studies examining the simultaneous effect of instrumented measures of both variables on growth observe a significant impact for institutional quality, but not trade. This they often ascribe to the “primacy” of institutions. In this paper, we revisit the argument by employing an IV estimator and a “modern” panel data technique, system GMM, to investigate the partial effect of trade and institutions on economic growth in Sub-Saharan Africa (SSA), for the period 2000 – 2016. Using IV-2SLS, our findings confirm a positive impact for rule of law with no significant impact for trade. But then, our first-stage results show commonly used instruments for trade and institutions in the literature, which are also employed in this study, are themselves highly correlated, rendering our IV estimates unreliable. Using system GMM however, our findings indicate positive effect for trade and various measures of institutional quality on growth in SSA. Of measures of institutional quality, political stability and control of corruption are the most important followed by government effectiveness, rule of law and voice and accountability in that order.
Thesis(Master) --KDI School:Master of Public Policy,2018